2-Desacetyl-8-Epi-Xanthumanol-4-O-β-D-Galactopyranoside: The Potential Antitumour Sesquiterpenoidal Lactone from Xanthium spinosum Bark - Ansari, A.H.; Dubey, K.S. (Asian Journal of Chemistry, 2010)
Xanthium spinosum Linn is reported to be used against hydrophobia, rabies and intermittent fever. It has diuretic properties and is reported to cure diarrhoea and cancer. The ethylacetate-soluble fraction of the concentrated alcoholic extract of Xanthium spinosum, bark when worked up chromatographically, yielded a colourless amorphous powder, m.f. C21H32O9, M+ = 428 and m.p. 157-158°C. Various colour reactions, chemical degradations and spectroscopic studies identified it as 2-desacetyl-8-epr-xanthumanol- 4-O-β-D-galactopyranoside (I).